Exploring the effectiveness of smart school program as a policy innovation in South Sulawesi, Indonesia - Mardin, Nur Fadillah Rianti Handayani; Haning, Moch Thahir; Syahribulan, Syahribulan (Edelweiss Applied Science and Technology, 2024)
The Smart School program, a policy innovation implemented by the South Sulawesi Provincial Government in Indonesia, has been successfully adopted by schools in the region. This study aims to examine the factors contributing to the successful adoption of the Smart School program focusing on five key attributes: relative advantage, compatibility, complexity, trialability, and observability. A qualitative approach was employed, involving interviews with key informants from the Education Office and schools participating in the program. The findings reveal that the Smart School program has demonstrated a significant relative advantage compared to previous educational practices, improving the accessibility and quality of education, enhancing school administration efficiency, and fostering the development of students' digital skills. The program's compatibility with existing values, past experiences, and the needs of potential adopters has facilitated its adoption. Despite some challenges related to technological infrastructure and teacher training, the overall complexity of the program is not considered a significant barrier to its adoption. The trialability of the program has played a crucial role in its success, allowing schools to experiment with technology integration before fully committing to the program. The observability of the program's positive outcomes has also encouraged schools to embrace and implement the Smart School program. The study concludes that the successful adoption of the Smart School program can be attributed to its alignment with the five attributes of innovation diffusion. The program's success highlights its potential as a model for policy innovation in the education sector. Recommendations for sustaining and enhancing the program's success include ongoing investment in technological infrastructure, targeted teacher training, continuous stakeholder engagement, and the establishment of a platform for sharing best practices among schools.